A multi-phase intervention study of sports bra prescription for elite UK female athletes preparing for the Tokyo Olympics and Paralympics - Wakefield-Scurr, J.; Sanchez, A.; Jones, M.; Hockley, L.; Biswas, A.; Johnson, F.; Roberts, E. (Research in Sports Medicine, 2022)
Athletes report poor breast/bra knowledge, breast pain, sports bras causing lacerations and chafing, negatively affecting sports performance. No bra interventions to address these issues are reported. Working with 142 UK female athletes preparing for Tokyo Olympics/Paralympics (27 sports), this multi-phase intervention assessed breast/bra knowledge, preferences, issues via surveys and breast/bra assessments. Data were used to develop two sports bras. A total of 112 athletes were prescribed one of the new bras through individual assessments. After four weeks, wear athletes completed evaluations. Pre-intervention breast/bra knowledge was low (83% =average), multiple breast/bra issues were reported and most athletes wore ill-fitting, loose bras, offering limited support. Post-intervention, 63% reported improved knowledge and 97% reported their prescribed bra as better than their original bra. Eighty-seven per cent reported benefitting from this intervention, with 17% reporting improved performance. This intervention effectively assessed sports bra needs, developed and implemented solutions, which improved knowledge and potentially performance for some UK athletes.